Programming Arduino: Getting Started With Sketches - Monk, Simon (McGraw-Hill, 2022)
An up-to-date guide to Arduino programming-no experience required!This fully updated guide shows, step by step, how to quickly and easily program all Arduino models using its modified C language and the Arduino IDE. You will learn how to configure hardware and software, write your own sketches, work with built-in and custom Arduino libraries, and develop apps for the Internet of Things. This edition features new coverage of using Arduino as a framework for programming other popular boards.Electronics guru Simon Monk gets you up to speed quickly, teaching all concepts and syntax through simple language and clear instruction designed for absolute beginners. Programming Arduino: Getting Started with Sketches, Third Edition features dozens of easy-to-follow examples and high-quality illustrations. All of the sample sketches featured in the book can be used as-is or modified to suit the reader's needs.Screenshots, diagrams, and source code illustrate each techniqueAll sample programs in the book are available for downloadWritten by a well-known hobbyist and experienced author